Cultural uncertainty as moderator of the organizational formalization puzzle - Hassan, Arif (2016)
Examining the complex role of formalization within a globalized context, we develop and test a new multi-level theory to address the positive and negative effects of formalization on organizational citizenship behavior (OCB). We review classic assumptions of culture-fit theories that argue that organizational practices are most effective if they match the larger technological and cultural context. We argue that there is a complex dynamic in that formalization has negative associations with OCB in national contexts that are relatively certain but positive associations with OCB in contexts of higher environmental uncertainty. A three-level hierarchical linear modeling analysis of data from 7,537 employees in 267 organizations across 17 countries supports our hypotheses. In nations with greater levels of uncertainty, formalization is positively associated with voice OCB. Effects on helping are more complex and appear masked by other culture-level dimensions. Our findings emphasize the need for further study of the dynamics between national contexts, organizational cultures and individual behavior.